2019
DOI: 10.1073/pnas.1908600116
|View full text |Cite
|
Sign up to set email alerts
|

Successive passaging of a plant-associated microbiome reveals robust habitat and host genotype-dependent selection

Abstract: There is increasing interest in the plant microbiome as it relates to both plant health and agricultural sustainability. One key unanswered question is whether we can select for a plant microbiome that is robust after colonization of target hosts. We used a successive passaging experiment to address this question by selecting upon the tomato phyllosphere microbiome. Beginning with a diverse microbial community generated from field-grown tomato plants, we inoculated replicate plants across 5 plant genotypes for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(99 citation statements)
references
References 66 publications
8
90
1
Order By: Relevance
“…The resulting phyllosphere microbiota was harvested and transplanted to new (uninoculated) tomato plants for the next passage. The authors observed a significant shift in microbiota composition and reduction of bacterial diversity after four passages, suggesting gradual microbial community selection and adaptation (Morella et al, 2020). Similarly, an experimental evolution study in M. truncatula showed that nitrogen-fixing rhizobia cross-inoculated to Medicago plants for five generations adapt to the host better than the ancestral strains do (Batstone et al, 2020).…”
Section: Sources Of the Phyllosphere Microbiotamentioning
confidence: 93%
See 1 more Smart Citation
“…The resulting phyllosphere microbiota was harvested and transplanted to new (uninoculated) tomato plants for the next passage. The authors observed a significant shift in microbiota composition and reduction of bacterial diversity after four passages, suggesting gradual microbial community selection and adaptation (Morella et al, 2020). Similarly, an experimental evolution study in M. truncatula showed that nitrogen-fixing rhizobia cross-inoculated to Medicago plants for five generations adapt to the host better than the ancestral strains do (Batstone et al, 2020).…”
Section: Sources Of the Phyllosphere Microbiotamentioning
confidence: 93%
“…Further in vitro experiments that monitor the growth of pathogen and microbiota strains in leaf homogenates sprayed with buffer or SynCom microbiota suggest that microbial interaction and fertilization‐induced host status are both important for determining the strength of phyllosphere microbiota‐mediated pathogen protection (Berg and Koskella, 2018). In addition to disease protection, phyllosphere microbiota can influence many other plant traits, including nutrient acquisition (e.g., nitrogen fixation (Mattos et al, 2008; Miyauchi et al, 2008)), adaptation to abiotic stresses (e.g., drought, ultraviolet, and frost tolerance (Lindow, 1987; Kumar et al, 2016; Arun et al, 2020)), and plant metabolic functions (Gargallo‐Garriga et al, 2016) (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Both A. brasilense HM053 and ipdC data was loosely clustered at opposite ends of iron values measured in seeds (30-130 nmols iron), whereas non-inoculated control data spanned the entire range of values. Recent studies in tomato indicate early treatments with inoculums can reshape the diversity of the soil microbiome favoring dominance of the inoculum whereas non-inoculated plants can exhibit a broad spectrum of microbiome diversity [43].…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the effects of genetic variance among hosts could be different, and interestingly, the divergence of host genetics in the O-A group was lower than that among O-Y hybrids ( Figure S4a), which might partly explain the observed filtering process. When the living environments and microbial populations are controlled, the influences of host genetics on microbial compositions have also been detected in other animals and plants [68,69]. However, the composition of resultant output microbiota is always determined by the input species [70].…”
Section: Discussionmentioning
confidence: 99%